A Multi-Omics Study of Familial Lung Cancer: Microbiome and Host Gene Expression Patterns - Chen, Ying; Huang, Yunchao; Ding, Xiaojie; Yang, Zhenlin; He, Liang; Ning, Mingjie; Yang, Zhenghong; He, Daqian; Yang, Lijuan; Liu, Zhangyi; Chen, Yan; Li, Guangjian (Frontiers in Immunology, 2022)
Background Inherited susceptibility and environmental carcinogens are crucial players in lung cancer etiology. The lung microbiome is getting rising attention in carcinogenesis. The present work sought to investigate the microbiome in lung cancer patients affected by familial lung cancer (FLC) and indoor air pollution (IAP); and further, to compare host gene expression patterns with their microbiome for potential links. Methods Tissue sample pairs (cancer and adjacent nonmalignant tissue) were used for 16S rRNA (microbiome) and RNA-seq (host gene expression). Subgroup microbiome diversities and their matched gene expression patterns were analyzed. Significantly enriched taxa were screened out, based on different clinicopathologic characteristics. Results Our FLC microbiome seemed to be smaller, low-diversity, and inactive to change; we noted microbiome differences in gender, age, blood type, anatomy site, histology type, TNM stage as well as IAP and smoking conditions. We also found smoking and IAP dramatically decreased specific-OTU biodiversity, especially in normal lung tissue. Intriguingly, enriched microbes were in three categories: opportunistic pathogens, probiotics, and pollutant-detoxication microbes; this third category involved Sphingomonas, Sphingopyxis, etc. which help degrade pollutants, but may also cause epithelial damage and chronic inflammation. RNA-seq highlighted IL17, Ras, MAPK, and Notch pathways, which are associated with carcinogenesis and compromised immune system. Conclusions The lung microbiome can play vital roles in carcinogenesis. FLC and IAP subjects were affected by fragile lung epithelium, vulnerable host-microbes equilibrium, and dysregulated immune surveillance and response. Our findings provided useful information to study the triple interplay among environmental carcinogens, population genetic background, and diversified lung microbiome.